2020
DOI: 10.1097/md.0000000000023669
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted study of hospital variables and interventions to improve inpatient satisfaction in a multi-hospital system

Abstract: Knowing the areas of service, actions, and parameters that can influence patient perception about a service provided can help hospital executives and healthcare workers to devise improvement plans, leading to higher patient satisfaction. To identify inpatient satisfaction determinants, assess their relationships with hospital variables, and improve patient satisfaction through interventions. We studied the inpatient population of an eight-hospital tertiary medical center in 2015. The sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Nurses can leverage communication tools like the AIDET framework (Acknowledge, Introduce, Duration, Explanation, and Thank You), developed by the Studer Group ( 2005 ), to enhance their interactions with patients. It has gained traction in recent training programs worldwide (Puppala et al, 2020 ). Studies, particularly in Thailand, have demonstrated the potential of AIDET to enhance patients’ experience and care delivery (Panchuay et al, 2023 ; Thangkratok et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses can leverage communication tools like the AIDET framework (Acknowledge, Introduce, Duration, Explanation, and Thank You), developed by the Studer Group ( 2005 ), to enhance their interactions with patients. It has gained traction in recent training programs worldwide (Puppala et al, 2020 ). Studies, particularly in Thailand, have demonstrated the potential of AIDET to enhance patients’ experience and care delivery (Panchuay et al, 2023 ; Thangkratok et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The AIDET framework was first presented by Studer Group ( 2005 ) and became widely used in training for healthcare professions over recent years. Puppala et al ( 2020 ) demonstrated that the AIDET tool is a focused, directed structure for provider-patient communications. The evidence listed under AIDET is a shorthand for a very effective technique for talking to persons who are frequently worried, anxious, and feeling vulnerable (Palombi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%